Assessing the Genetic Diversity of Mycobacterium tuberculosis Strains in Kerala, India: A Comprehensive Study - Sreeja Nair 1*; Seema Oommen2; Vidya Pai3 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Understanding the epidemiological and clinical characteristics of different tuberculosis strains is crucial for developing improved diagnostic tools, drugs, and vaccines for tuberculosis management. This study aimed to investigate the molecular epidemiology of Mycobacterium tuberculosis using spoligotyping, a widely used molecular typing method, to understand the genetic diversity and transmission dynamics of M. tuberculosis, on isolates obtained from patients with pulmonary tuberculosis in central Kerala. Methods: In a prospective study at a tertiary care hospital, 404 respiratory specimens from patients with symptoms suggestive of TB were collected. Specimens underwent Ziehl- Neelsen staining, culture in liquid (BD BACTEC™ MGIT™) and solid (Lowenstein-Jensen) media, and standard drug susceptibility testing with the MGIT system. Molecular analysis involved conventional PCR amplification of genomic DNA to generate sufficient genetic material for analysis, using species-specific and primers targeting the direct repeat region, followed by spoligotyping to assess the genetic diversity of the M. tuberculosis strains. Results: Out of 404 samples from individuals with suspected pulmonary TB, Mycobacteria were cultured from 48 [11.9%] of the samples. Amongst the 48 culture-positive M. tuberculosis isolates, 20 (41.66%) were sensitive to all five first-line anti-TB drugs, and 3 (6.2%) were resistant to all five drugs. Spoligotyping of the 47 isolates showed that 36.1% [n=17] of the isolates belonged to the M. tuberculosis EAI3 (East African-Indian) family, followed by 27.6% (n=13) M. tuberculosis EAI5 and 21.2% (n=10) M. tuberculosis CAS (Central Asia). Other families observed in this study, although less prevalent, were M. tuberculosis Beijing, 8.5% (n=4), family 33, 4.3% (n=2), and Mycobacterium bovis-BCG family, 2.1% (n=1). Conclusion: This study explored the genetic diversity and distribution of circulating M. tuberculosis strains in central Kerala. Genotyping M. tuberculosis strains provides valuable insights into TB transmission and progression, which can inform the development of effective public health control strategies.